Ceratostema gualaquizensis (Ericaceae: Vaccinieae), a new species from Ecuador known from previously misidentified specimens and new insights on Ceratostema loucianae - Jiménez, Marco M.; Iturralde, Gabriel A.; Kuethe, J.r.; Lapo-González, Nadia; Baquero, Luis E.; Vélez-Abarca, Leisberth; Garzón-Suárez, Henry X. (Phytotaxa, 2024)
A species of Ceratostema new to science from southern Ecuador, is described and illustrated as part of ongoing research on biodiversity in the Cordillera Real de Los Andes. Ceratostema gualaquizensis is distinguished by the convex leaves with folded margins at the base, and the axillary, solitary, and tubular flowers with a slightly 5-ribbed corolla that is magenta with apically black lobes. Furthermore, we provide additional information on the newly described Ceratostema loucianae. The taxonomic similarities of these two species are discussed and information about their distribution, habitat, and conservation status are provided. Both species are being sold and cultivated with erroneous/fictitious names by nurseries and private collections, information of which is provided in this paper.